Tree Height Reduction After Selective Logging in a Tropical Forest. (1st April 2016) - Rutishauser, Ervan; Hérault, Bruno; Petronelli, Pascal; Sist, Plinio
Abstract: By harvesting scattered large trees, selective logging increases light availability and thereby stimulates growth and crown expansion at early‐life stage among remnant trees. We assessed the effects of logging on total and merchantable bole ( i.e ., lowest branch at crown base) heights on 952 tropical canopy trees in French Guiana. We observed reductions in both total (mean, −2.3 m) and bole (mean, −2.0 m) heights more than a decade after selective logging. Depending on local logging intensity, height reductions resulted in 2–13 percent decreases in aboveground tree biomass and 3–17 percent decreases in bole volume. These results highlight the adverse effects of logging at both tree and stand levels. This decrease in height is a further threat to future provision of key environmental services, such as timber production and carbon sequestration.